Vulnerability curves for masonry buildings affected by hyperconcentrated flows as natural disaster risk management tools for the quantification of material damage - Jara, A. (2022)
The damage assessment caused by floods, earthquakes, hurricanes among others phenomenons in the world are analyzed with methodologies such as "Vulnerability curves". In Peru, disasters caused by hyperconcentrated flows are alarming due to a climatic variability such as the "El Nio Costero"phenomenon. Therefore, this research has developed vulnerability curves for 1 and 2-story confined masonry buildings in Urb. San Idelfonso, Ica - Peru; linking the variables: flow depth, associated with the event produced by heavy rains at the top of the "Quebrada Cansas"caused by the "El Nio Costero"phenomenon in 2017, and the percentage of the damage based on the methodology of the United States Army Corps of Engineers (USACE), whose formula is the repair value and total building value. The monetary amounts and items of the buildings are obtained from the RM 415-2017-VIVIENDA of the Ministry of Housing, Construction and Sanitation of Peru. The process consisted of hydrological modeling in HEC-HMS, hydraulic modeling in FLO-2D, damage percentage estimate and vulnerability curves production. Finally, the vulnerability curves for hyperconcentrated flows were contrasted with similar studies regarding curves for flooding and debris flow. The results of the investigation showed that the "El Nio Costero"phenomenon in 2017 had an economic impact of at least 1.3 million soles in Urb. San Idelfonso. In addition, at least 24 buildings had a complete damage and 21 buildings an extensive damage.